2022
DOI: 10.1186/s13034-022-00540-4
|View full text |Cite
|
Sign up to set email alerts
|

Distance learning during the COVID-19 pandemic for children with ADHD and/or ASD: a European multi-center study examining the role of executive function deficits and age

Abstract: Background One of the COVID-19 pandemic consequences that has affected families the most is school lockdowns. Some studies have shown that distance learning has been especially challenging for families with a child with neurodevelopmental disorders such as ADHD or ASD. However, previous studies have not taken the heterogeneity of these disorders into account. The aim of the present study was therefore to investigate differences between families with a child with ADHD, ASD, or both conditions, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Finally, it should be noted that the present study only included adolescents. The results, therefore, cannot be generalized to samples of younger children, especially as previous research has shown that the challenges associated with distance learning decrease with age [24], although not as much for those with ADHD/ASD compared to those without [9].…”
Section: Strengths and Limitationsmentioning
confidence: 82%
See 4 more Smart Citations
“…Finally, it should be noted that the present study only included adolescents. The results, therefore, cannot be generalized to samples of younger children, especially as previous research has shown that the challenges associated with distance learning decrease with age [24], although not as much for those with ADHD/ASD compared to those without [9].…”
Section: Strengths and Limitationsmentioning
confidence: 82%
“…Previous quantitative studies have shown that families with a child with ADHD/ASD experience more negative effects of distance learning compared to those without a neurodiverse child [4][5][6][7][8][9]. This finding has been explained by the fact that children with neurodevelopmental disorders, especially those with ADHD, have more academic difficulties compared to controls [11,12].…”
Section: Negative Effects Of Distance Learningmentioning
confidence: 98%
See 3 more Smart Citations